Modeling Azerbaijan's inflation and output using a factor-augmented vector autoregressive (FAVAR) model - Vugar Rahimov; Nijat Guliyev; Vugar Ahmadov (Graduate Institute of International and Development Studies, 2020)
In this study, we build and use a factor-augmented vector autoregressive (FAVAR) model to forecast inflation and output in Azerbaijan. The FAVAR model is particularly effective in data-rich environments, alleviating the curse of dimensionality of the standard VAR model and handling omitted variable bias. Using 77 variables for factor extraction and quarterly data for the period 2003 to 2018, we build several multivariate models, including a FAVAR model, and compare their performance with that of a benchmark univariate model. Our findings show that almost all of the multivariate models underperform in comparison with the univariate model. This result is in line with the literature, which finds that simple models are better forecasters of some macroeconomic variables, especially inflation. We acknowledge that the results might be affected by the relatively short length of the sample period and existence of irregularities in the data.
Keywords: 330; Inflation; Wirtschaftsprognose; VAR-Modell; Aserbaidschan